Handling Of Traffic Criminal Actions At The Traffic Unit Of Asahan Resort Police - Muhammad Salim Fauzi Lubis; Aqsha (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
As a state based on law in achieving a goal of national and state life in order to achieve public welfare. That road traffic and transportation as part of the national transportation system must develop its potential and role to realize security, safety, order, and smooth traffic and road transportation in the context of supporting economic development and regional development. There are many problems related to criminal acts in traffic, ranging from mild to severe. This study aims to determine how the process of handling traffic crimes, how to apply sanctions based on their violations, and to find out the role of the police to minimize the occurrence of traffic crimes. The formulation of the problems raised in this paper are: 1) How is the process of handling criminal cases that cause loss of human life in traffic accident cases at the Asahan Police Traffic Unit, 2) How is the application of criminal sanctions against traffic violations at the Traffic Unit Asahan Police, 3) What are the efforts made by the Asahan Police Traffic Unit in tackling traffic violations. This research is a type of empirical legal research (field research), namely research conducted in the field. The type of data used is primary data by conducting direct field studies. The type of data used is primary data by conducting a direct field study, based on the results of the research from the title above, it can be seen that for proof of the high level of crime in traffic. And we can know the regulations that discuss traffic crimes, namely Law No. 22 of 2009 concerning Road Traffic and Transportation